PENGARUH LEVERAGE, EARNINGS VOLATILITY DAN PAJAK PENGHASILAN PADA NILAI PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BEI - Cahyani, A. A. Istri Mega; Astika, Ida Bagus Putra (E-Jurnal Akuntansi; Vol 20 No 2 (2017), 2017)
This study aimed to get empirical evidence of the effect of leverage, earnings volatility and income tax on the value of companies listed in Indonesia Stock Exchange 2010-2014. The sample selection used was random sampling technique that is obtainable 14 (fourteen) manufacturing companies. With a data analysis technique used is multiple linear regression analysis were supported by statistical test F, t statistical test and the coefficient of determination. The results of this study indicate that leverage and earnings volatility negatively affect the value of companies listed on the Indonesia Stock Exchange in 2010-2014, while the income tax positive effect on the value of companies listed in Indonesia Stock Exchange 2010-2014.
Keywords: leverage; earnings volatility; income tax; the value of the company